2016
DOI: 10.1093/ptep/ptw160
|View full text |Cite
|
Sign up to set email alerts
|

Probing SUSY with 10 TeV stop mass in rare decays and CP violation of kaon

Abstract: We probe the SUSY at the 10 TeV scale in the rare decays and the CP violation of the kaon. We focus on the processes of K L → π 0 νν and K + → π + νν combined with the CP violating parameters ǫ K and ǫ ′ K /ǫ K . The Z-penguin mediated by the chargino loop cannot enhance K L → π 0 νν and K + → π + νν because the left-right mixing of the stop is constrained by the 125 GeV Higgs mass. On the other hand, the Z-penguin mediated by the gluino loop can enhance the branching ratios of both K L → π 0 νν and K + → π + … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 112 publications
(167 reference statements)
1
61
0
Order By: Relevance
“…where f K is the K-meson decay constant; P V LL 1 ≈ 0.48 is the nonperturbative QCD effects, and the factor (α s (m H 6 )/α 2 (m t )) 6/21 is the renormalization group (RG) evolution from the m H 6 scale to the m t scale. Since the Kaon indirect CP violation parameter K is associated with V * ts V td in the SM, we scale the parameters (g † g) 21 with the (V * ts V td ) −1 factor. Thus, the mass difference between K L and K S and K can be obtained as:…”
Section: B Ew Gauge Couplings To Hmentioning
confidence: 99%
See 2 more Smart Citations
“…where f K is the K-meson decay constant; P V LL 1 ≈ 0.48 is the nonperturbative QCD effects, and the factor (α s (m H 6 )/α 2 (m t )) 6/21 is the renormalization group (RG) evolution from the m H 6 scale to the m t scale. Since the Kaon indirect CP violation parameter K is associated with V * ts V td in the SM, we scale the parameters (g † g) 21 with the (V * ts V td ) −1 factor. Thus, the mass difference between K L and K S and K can be obtained as:…”
Section: B Ew Gauge Couplings To Hmentioning
confidence: 99%
“…Since it is not our purpose to show the generic CP phase effects of y in this study, we assume that y is a real matrix in the following numerical analysis, unless stated otherwise. Taking the Wolfenstein's parametrization [13] as an input, the CP phase of the CKM matrix appears in V td and V ub , and the Kaon CP violation in the SM arises from Im(V * ts V td ); therefore, when the K constraint is considered, we can simply focus on the V td related effects in (g † g) 21 . In addition, because ∆M K may cause a strict constraint on the free parameters, we should also pay attention to the effects, which arise from a large CP-conserving CKM factor.…”
Section: B Ew Gauge Couplings To Hmentioning
confidence: 99%
See 1 more Smart Citation
“…They could be a signal to test the scenario. In the MSSM, such a scenario is also realized when the off-diagonal components of the trilinear SUSY-breaking couplings are large [33][34][35].…”
Section: Z-penguin Dominated (Modified Z-coupling) Scenariomentioning
confidence: 99%
“…Indeed, theoretical studies have been performed in a number of NP models, with the outcome that in many NP scenarios it is possible to enhance ε /ε by an order to magnitude and resolve the tension. We refer the reader to the original publications for further details on Little Higgs models [29], supersymmetric models [30,31,32,33], simplified models with flavour changing Z or Z couplings [34,35], 331 models [36], vector-like quark models [37], and a model independent analysis [38]. A review can be found e. g. in [39].…”
Section: Pos(fpcp2017)042mentioning
confidence: 99%